A review of the current status and techniques of allogeneic bone marrow transplantation for treatment of leukaemia. Issue 11 (November 1983) - Prentice, H G
Abstract : Bone marrow transplantation is now an accepted component in the overall therapy of acute and chronic (myeloid) leukaemia for some selected patients. Some of the obstacles to success have been partially overcome. Many advances in supportive care have been made. Pneumocystis carinii and herpes simplex infections are preventable. Effective decontamination of the gastrointestinal tract for bacteria and fungi is now readily achievable and may have reduced the risk of serious systemic infections. New antibiotics which, in combination, are effective in life-threatening infections are under study. Recent developments in the prevention or amelioration of graft versus host disease (GvHD) have included T lymphocyte depletion in the donor marrow and the use of the fungal polypeptide cyclosporin A. Less than 10% of patients would now be expected to succumb to this complication. Outstanding problems remaining to be resolved are the improvement in the antileukaemic conditioning prior to transplantation and the prevention or treatment of cytomegalovirus infection in the seropositive recipient. This infection can cause pneumonitis and is currently the single most frequent transplant related cause of mortality.